Mathematical Logical Intelligence, Visual-Spatial Intelligence, and Learning Motivation: Which Variabels Affect Mathematics Problem Solving Ability? - Hertanti, Alfiramita; Aprisal, Aprisal; Fitriani, Fitriani; Urwatul Wustqa, Dhoriva (JTMT: Journal Tadris Matematika, 2024)
This study aimed to investigate the effect of mathematical-logical intelligence, visual-spatial intelligence, and learning motivation simultaneously toward student’s problem solving ability. The population in this study was the grade XI students in Gowa regency and the sample was 353 students. The sampel was drawn using proportional stratified random sampling. The instrument used to collect data was mathematical-logical intelligence test, visual-spatial intelligence test, problem solving ability test, and questionnaire of learning motivation. Multiple regression analysis were employed in this study. The result of this study showed that students have moderate mathematical-logical intelligence and visual-spatial intelligence, high learning motivation, and low problem solving ability. There was positive effect of mathematical-logical intelligence, visual-spatial intelligence, and learning motivation simultaneously toward student’s problem solving ability. It could be seen by regression coefficient R = 0,334. The coefficient of determination R2 = 0,111 implyed that mathematical-logical intelligence, visual-spatial intelligence, and learning motivation simultaneously contributed to 11,1% of student’s problem solving ability.